2023
DOI: 10.3390/genes14020420
|View full text |Cite
|
Sign up to set email alerts
|

A Cell System-Assisted Strategy for Evaluating the Natural Antioxidant-Induced Double-Stranded DNA Break (DSB) Style

Abstract: Natural antioxidants derived from plants exert various physiological effects, including antitumor effects. However, the molecular mechanisms of each natural antioxidant have not yet been fully elucidated. Identifying the targets of natural antioxidants with antitumor properties in vitro is costly and time-consuming, and the results thus obtained may not reliably reflect in vivo conditions. Therefore, to enhance understanding regarding the antitumor effects of natural antioxidants, we focused on DNA, one of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…1A). We previously reported that LIG4 À/À or RAD54 À/À cells exhibit greater sensitivity to DSBinducing agents than do wild-type cells [14,17]. Thus, our results suggest that the cytotoxicity associated with arsenic exposure is not caused by DSB induction per se.…”
Section: Arsenic Does Not Affect End-joining Pathwayssupporting
confidence: 53%
See 3 more Smart Citations
“…1A). We previously reported that LIG4 À/À or RAD54 À/À cells exhibit greater sensitivity to DSBinducing agents than do wild-type cells [14,17]. Thus, our results suggest that the cytotoxicity associated with arsenic exposure is not caused by DSB induction per se.…”
Section: Arsenic Does Not Affect End-joining Pathwayssupporting
confidence: 53%
“…Double-strand breaks are the most lethal type of DNA lesions, occurring as one-or two-ended [10][11][12][13]. Ionizing radiation and DNA topoisomerase II (Top2) inhibitors (such as etoposide) induce two-ended DSBs [14]. One-ended DSBs are unique in that they arise when replication forks collide with single-stranded breaks or DNA crosslinks [14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations